Assessing the Current State of Tourism Development in Gashaka Gumti National Park - Silas, Akafa Konde; Madaki, Kanati; Chibuma, Gani Saidu (Kwaghe International Journal of Sciences and Technology, 2025)
This study assesses the current state of tourism development in Gashaka Gumti National Park, Nigeria. Questionnaires were administered across all communities officially recognized by the National Park authority to obtain first-hand perspectives from community members. Data collected covered respondents’ socio-economic characteristics, available tourist attractions, and supporting facilities. Findings revealed that the park’s rich biodiversity, including diverse forest ecosystems, wildlife, and bird species serves as a primary attraction for tourists. Within the surrounding communities, facilities such as schools, health centres, television viewing centres, electricity, and public tap water were identified; however, only about 10% of respondents reported access to tap water, while more than 50% relied on rivers and streams. Most of these amenities were provided by the Adamawa and Taraba State governments as well as the Local Government Areas of Toungo, Gashaka, and Sardauna. The study further noted that tourists were particularly drawn to the availability of standard restaurants and both indoor and outdoor sporting facilities in the park. To strengthen tourism development, the paper recommends enhancing partnership programmes between the National Park and local communities, alongside improvements in basic infrastructure and service delivery, to foster sustainable tourism growth.